Understanding Purchasing Decisions for Skintific Products through Digital Marketing, Product Diversity, and Pricing - Widiawati, Kristiana; Yuniasti, Nenden (Westscience Press, 2025)
Increase in the number of product uses skincare global fast making brand skincare need to consider digital marketing, product innovation, and the right price to attract potential consumers. This research aims to determine the effect digital marketing, product diversity, and price on purchasing decisions. This research is quantitative research conducted through an online survey using sampling techniques purposive sampling against 100 respondents who have been determined by the criteria; product consumers skincare aged 18-35 years, domiciled in Bekasi City, and have purchased or used Skintific products. Data analysis used the SPSS version 27 application. Result of research shows that digital marketing, product diversity, and price have a partially positive and significant influence on purchasing decisions for Skintific products in Bekasi City. The results digital marketing, product diversity, and price have a positive and significant influence together or simultaneously on purchasing decisions for Skintific products in Bekasi City. The results show that the higher the digital marketing, product diversity, and price, the greater the purchasing decision.